PERANCANGAN JALAN LAYANG AKSES TERMINAL A MANGKANG SEMARANG - Fazar Nurrianto; Kuncoro Adhi Iswanto; Epf. Eko Yulipriyono; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2013)
Intensiveness of Traffic density on the road Walisongo plus increasingly dense traffic of vehicles in and out of A terminal of Mangkang trigger increased of traffic delays, so need ideas to reduce the delay with the construction of  flyover as access to exit/ enter the Mangkang terminal. Construction of flyovers are planned using reinforced concrete and built at the entrance and exit of the A terminal of Mangkang. The flyover is planned to span 52 m, bordered by two abutments. Overpass with a width 8.3 m is divided into 2 lanes of traffic one direction (1 piece overpass) with each traffic lane width of 2.75 m and a width of each pavement on the right side and left the overpass 1 m. Construction on the overpass is planned to use the overpass slab of reinforced concrete, girder extends from PCI Girder. Construction under cover of reinforced concrete abutments. Using bored pile foundation with 1 m of diameter. The depth of bored pile foundation on the abutment is 12 m. The design of  the flyover also planned approach roads or highways with a length oprit each to oprit the terminal exit 185 m and oprit the terminal entrance is 143 m. In oprit, flyover is  planned using laston flexible pavement with 150 mm thick and 100mm thick layer of foundation under CBK (Mixed Concrete Slim) with a concrete compressive strength of 5 MPa (50 kg/m2). Based on the calculation of the Budget Plan (RAB) for the construction of two flyovers pieces cost of Rp. 40.078.193.427,- (Forty Billion Seventy Eight Million One Hundred Ninety Three Thousand Four Hundred Twenty-seven dollar) cost including VAT 10%, while for the time of the construction was completed over 18 months (72 weeks).